Pharmacognostical And Physicochemical Evaluation On Stem Bark Of Limonia Acidissima Linn - BHUPENDRA KUMAR KUMAWAT; TARA CHAND; YOGENDRA SINGH (International Journal of Pharma and Bio Sciences, 2012)
Limonia acidissima, Linn belonging to family Rutaceae commonly known as wood apple and elephant apple has been studied to compare and give detailed reports on pharmacognostical studies like macroscopical and microscopical characters, powder microscopy, physico-chemical constants like total ash value (10.00 %w/w), acid insoluble ash value (5.5%w/w), water soluble ash value (2.16%w/w), sulphated ash value (16.30%w/w), water soluble extractive value (5.7%w/w), ethanol soluble extractive value (2.7%w/w), loss on drying (7.55 %w/w) and fluorescence analysis. Bark shows microscopic characters like cork, cortex, medullary rays, sclerenchyma fibres, phloem, cambium and crystals.The above studies provide useful information in regard to its correct identity and evaluation, and help to differentiate from the closely related other species of Limonia acidissima, Linn.